Concentration of metals in water around roads: a case study in Southern Brazil - Vagner José Albuquerque; Caroline Müller; Marilia Hartmann; Paulo Afonso Hartmann (Discover Environment)
Abstract Roads can be sources of pollutants that can affect the environment. By exceeding the carrying capacity of the environment, metallic elements become a source of environmental pollution as they present themselves as substances with harmful and bioaccumulative properties. This study aimed to analyze the effects of proximity to roads on the occurrence and concentration of metallic elements in water. The study was conducted near the RS-135 highway in the state of Rio Grande do Sul, Southern Brazil. The water samples were collected in three environments with different influence of surface water runoff: (a) in water bodies near the RS-135 highway (six sampling points), (b) in water bodies in the agricultural systems around the RS-135 (three sampling points), and (c) in water bodies within the Sertão Municipal Natural Park (SMNP, three sampling points)). Two water samples were collected at each site, the first in October and the second in December 2022. The estimation of the presence and concentration of metal elements was carried out using inductively coupled plasma optical emission spectrometry (ICP-OES). Of the thirteen elements analyzed, eight metallic elements were detected: Al, Ca, Fe, K, Mg, Mn, Na and Zn. Three elements (Ca, Mg and Na) showed higher concentrations near the highway. Al, Fe and Mn were detected in concentrations above the limit considered environmentally acceptable for type II lentic water in Brazil. Our study shows that proximity to roads can increase the concentration of dissolved metals in surface waters, which can lead to pollution of the surrounding waters.